Državne rabe kulturnih pomenov za politične namene - Pušnik, Maruša (Javnost (Ljubljana), 2006)
In order to achieve specific political ends, such as for example the creation of national identity, a state can instrumentalize arbitrary and culturally specific concepts for political purposes. The article focuses on the plebiscite propaganda in Carinthia by two states, Austria and the Kingdom of Serbs, Croats and Slovenes before the 1920 plebiscite about the annexation of Carinthia to Austria. The plebiscite propaganda was the way of exhibiting political power of both states and it played a crucial role in the production of national people in Carinthia and in the construction of differences between them. Such use of communication practices by both states enabled nationality to be institutionalized and to decisively determine people's everyday lives. This case proves that the state can achieve through communication with its residents a widely accepted consensus when it transforms arbitrary cultural meanings into national ones and in this way creates and controls its own population. The outcome of the plebiscite should be understood as a product of such state-performed communication practices and not as a reflection of some pre-existing national will of Carinthians. Therefore, national border in Carinthia should not be seen as historical necessity, but as the product of the clash of the two state-building discourses that have at least from the plebiscite onwards produced national ideologies and in this regard prepared solid grounds for the reproduction of national differentiation.
Keywords: država; state; komuniciranje; communication; propaganda; politične komunikacije; Austria; Avstrija; Koroška; plebiscit; 1920